2011
DOI: 10.1039/c1mt00034a
|View full text |Cite
|
Sign up to set email alerts
|

The effects of protein crowding in bacterial photosynthetic membranes on the flow of quinone redox species between the photochemical reaction center and the ubiquinol-cytochrome c2 oxidoreductase

Abstract: Atomic force microscopy (AFM) of the native architecture of the intracytoplasmic membrane (ICM) of a variety of species of purple photosynthetic bacteria, obtained at submolecular resolution, shows a tightly packed arrangement of light harvesting (LH) and reaction center (RC) complexes. Since there are no unattributed structures or gaps with space sufficient for the cytochrome bc(1) or ATPase complexes, they are localized in membrane domains distinct from the flat regions imaged by AFM. This has generated a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…The redox state is affected by not only RC and cytbc 1 reactions, but also by transmembrane enzymes succinate dehydrogenase and NADH dehydrogenase ( Figure 5). The low-light and high-light limits for the cycling time, t RC , employed below are based on experimental observation (Woronowicz et al, 2011b(Woronowicz et al, , 2011aCrofts, 2004) instead of direct computation; the reported values of t RC implicitly combine the redox reactions of all enzymes interacting with the quinone/quinol pool, including NADH dehydrogenase. In a stationary state, the rate k ATP ðIÞ of ATP synthesis is equal to the rate k Q!QH 2 ðIÞ as stated in Equation (1), which according to Equations (11) and (13) can be expressed through the cycling time, t RC ðIÞ.…”
Section: Stage I: Light Absorption Excitation Energy Transfer and Qmentioning
confidence: 99%
See 3 more Smart Citations
“…The redox state is affected by not only RC and cytbc 1 reactions, but also by transmembrane enzymes succinate dehydrogenase and NADH dehydrogenase ( Figure 5). The low-light and high-light limits for the cycling time, t RC , employed below are based on experimental observation (Woronowicz et al, 2011b(Woronowicz et al, , 2011aCrofts, 2004) instead of direct computation; the reported values of t RC implicitly combine the redox reactions of all enzymes interacting with the quinone/quinol pool, including NADH dehydrogenase. In a stationary state, the rate k ATP ðIÞ of ATP synthesis is equal to the rate k Q!QH 2 ðIÞ as stated in Equation (1), which according to Equations (11) and (13) can be expressed through the cycling time, t RC ðIÞ.…”
Section: Stage I: Light Absorption Excitation Energy Transfer and Qmentioning
confidence: 99%
“…The low-light limit, t L , of the cycling time, t RC ðIÞ, is observed to range from 0.7 ms for the membrane of an LH2-minus mutant to about 3 ms for the LH2-rich chromatophores adapted to low-light growth conditions (Woronowicz et al, 2011b(Woronowicz et al, , 2011a. In the following, we assume t L ¼ 3 ms for the low-light growth vesicle shown in Figure 1.…”
Section: Stage I: Light Absorption Excitation Energy Transfer and Qmentioning
confidence: 99%
See 2 more Smart Citations
“…mesosomes [Pilhofer et al, 2010]) as discussed in detail in this written symposium. Even with these ICMs, many basic unanswerable questions regarding their biogenesis, maintenance and turnover remain [Drews and Niederman, 2002;Tucker et al, 2010;Woronowicz et al, 2011]. These may be relevant to ICM and micelle biogenesis in E. coli and higher eukaryotes.…”
Section: Putting Things Into Perspectivementioning
confidence: 99%